Comparison of lubrication conditions for grinding of mild steel with electroplated cBN wheel. (August 2017) - Kuffa, Michal; Kuster, Fredy; Wegener, Konrad
Abstract: Grinding low carbon steel with diamond is regarded to be not feasible due to its chemical affinity to iron. A workpiece with comparable low hardness 330 HV30 and low-carbon content is selected. Therefore, cBN is a suitable choice of a superabrasive and thus employed. Its advantages compared to conventional abrasives are higher material removal rate and less wear. The thermal behaviour of the cBN grinding wheel in different environmental conditions is examined. The dry grinding process with a cBN grinding wheel is discussed and compared to wet grinding, grinding with minimum quantity lubrication and CO2 cooling. Increase in material removal rate and low wear rates are targeted. An electroplated, monolayer cBN grinding wheel with open structure design guarantees higher cooling ability and enlarged space for chips. The wear behaviour of the grinding wheel and the thermal damage on the workpiece surface are investigated. Cutting forces and temperatures are measured during the process for different high feed rates and depth of cuts. The thermal damages are evaluated by microscopic texture analysis. Grinding wheel dust contamination and loading connected with a significant temperature increase could be observed under dry environment. Cleaning impact of cooling nozzle on grinding wheel surface led to decreased normal forces and better surface roughness. Cooling impact of minimum quantity lubrication and CO2 cooling appeared less significant than emulsion.